Commutativity of Addition in Prime Near-Rings with Right (Î¸,Î¸)-3-Derivations - Saed, Ikram A. (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
Let N be a near-ring and is a mapping on N . In this paper we introduce the notion of right ()-3-derivation in near-ring N. Also, we investigate the commutativity of addition of prime near-rings satisfying certain identities involving right ()-3-derivation.